(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2015)
Loratadine is an antihistaminic drug, used in the treatment of allergic inflammation. Poor bioavailability of the drug from conventional dosage forms is especially attributable to mucociliary clearance and transient residence time. These problems can be reduced by the employment of niosomal in situ gelling system. In situ gelling of niosomal drops was developed to maintain the drug localization for extended period of time. The niosomal in situ gel formulation was transformed into gel once it is instilled into the nasal cavity. Niosomes were formulated using various surfactants (span 20, 40, 60 and 80) in different ratios using thin film hydration technique. Niosomes were evaluated for particle size, drug entrapment efficiency and in-vitro drug release. Niosomes prepared using cholesterol and span 60 in the ratio 1:1 (F3) showed higher entrapment efficiency (94.87%) and in-vitro drug release (59.90%) was optimized. The optimized niosomes were developed into in situ gel (pH induced and thermoreversible). The gels were evaluated for gelling capability, pH, viscosity, drug content and in-vitro drug release. Ex-vivo permeation was performed for optimized in situ gels (G2 and T5). The flux (Jss) and Permeability Coefficient (Kp) was found to be higher for G2. Hence niosomal in situ gelling system may have its potential applications than the conventional nasal formulations and to improve the bioavailability of the drug through its longer residence time and ability to sustain drug release with minimal loss of drug.